Optimizing Intra-Organizational Knowledge Transfer: A Conceptual Framework Based on Success Factors and Conditions - Noura Ksentini; Abdelkader Dali (African Scientific Journal, 2025)
Abstract In today’s competitive and dynamic global landscape, an organization’s ability to innovate, adapt, and maintain a sustainable competitive advantage hinges on the effective transfer and sharing of knowledge within its own structures. Knowledge transfer, particularly within an organization, plays a pivotal role in fostering innovation, enhancing decision-making and ensuring continuity of expertise. Yet, without a structured and systematic approach to managing these intellectual assets, organizations may struggle to keep up with rapid changes, facing challenges such as high turnover, skill gaps, and the loss of critical knowledge when key employees leave. This research specifically focuses on identifying the key success factors influencing intra-organizational knowledge transfer in the Tunisian context, providing both conceptual insights and practical recommendations. By conducting a quantitative study across 60 companies in various industries, this paper not only explores the characteristics of the knowledge being transferred but also examines the roles of different stakeholders involved, including their relationships and capabilities. These insights aim to build a framework that organizations can utilize to optimize their knowledge management processes, ultimately supporting long-term growth and operational resilience. Keywords: Knowledge Transfer, Intra-organizational Knowledge Transfer, Success Factors, Tunisian Context, Knowledge Management.